Synthesis, characterization and antibacterial activity of bis thiourea derivatives - Ainaa Nadiah, Abd Halim (Universiti Malaysia Sarawak, UNIMAS, 2013)
A series of bis(thiourea) derivatives were successfully synthesized by reaction of benzene-1,4-dicarbonyl isothiocyanate intermediates, with amino acid and aromatic amine to afford thiourea 20-24 with overall yields of 11–58%. The structures of the synthesized compounds were characterized by infra red spectroscopy (FTIR), 13C nuclear magnetic resonance (NMR), and 1H NMR spectroscopy. The antibacterial activities of thiourea 20-24 were investigated on gram-negative bacteria, Escherichia coli using turbidimetric kinetic method. Minimum inhibition concentration (MIC) values of the compounds toward the bacteria were determined. The result obtained in this study indicated that only N1,N4- bis(phenylcarbamothioyl)terephthalamide 22 showed antibacterial activity against E. coli compared with other synthesized compounds.